2022
DOI: 10.12968/bjcn.2022.27.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Improving sepsis recognition through use of the Sepsis Trust's community screening tool

Abstract: Sepsis is associated with high levels of morbidity and mortality. All healthcare professionals have a responsibility to ensure they have sufficient knowledge to effectively screen patients for signs and symptoms of sepsis. In the community setting, screening for sepsis can be challenging, due to the complexity within the patient population and difficulties associated with observation for changes in the patient's condition. The Sepsis Trust community nursing sepsis screening tool provides decision-making suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 37 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…For example, Pritchard and Velayudhan (2011) reported that only 17% of community nurses and 36% of primary health care nurses were assessing patients for cognitive decline due to a lack of standards and consistency for dementia education in pre‐registration training. The role of nurses in educating patients about early warning signs of deterioration was noted by several authors (Baker, 2022; Ekong et al., 2016; Georgiev et al., 2019).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, Pritchard and Velayudhan (2011) reported that only 17% of community nurses and 36% of primary health care nurses were assessing patients for cognitive decline due to a lack of standards and consistency for dementia education in pre‐registration training. The role of nurses in educating patients about early warning signs of deterioration was noted by several authors (Baker, 2022; Ekong et al., 2016; Georgiev et al., 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the introduction of ‘early warning systems’ has shown to assist community nurses to identify the need for urgent referral to accident and emergency services (Nazarko, 2019; Tucker & Lusher, 2018). For example, in the United Kingdom, a national enquiry reported that around 70% of sepsis cases originated in the community setting (Baker, 2022). This prompted the implementation of National Health Service patient safety alert that required hospital and ambulance services to use the track‐and‐trigger recognition system for clinical deterioration (NEWS2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations